Analisis Kebutuhan Modul Elektronik Mata Pelajaran IPS Untuk Siswa SMP - Mutiara Danirmala; Asrowi Asrowi; Akhmad Arif Musadad (Teknodika, 2019)
This research is a preliminary research with the aim to determine the needs of the students of SMP Islam Diponegoro regarding the media that need to be developed for social studies teaching and learning process. The method used in this research is survey method. The data analysis technique used was descriptive qualitative. Based on interviews and observations that have been conducted, it can be seen that the amount of material, the limited amount of learning resources, and the use of monotonous media are all obstacles in the social studies teaching and learning process. The results of the questionnaire given to students showed that as many as 54% of students need an electronic module as their learning media, and about 66% of the students stated that the nature condition of Indonesia is a difficult material. Therefore, the development of instructional media in the form of electronic module is needed as a tool to communicate the subject material interactively and achieve the goals of learning. The electronic module can be developed supported by theschool facilities and can be used independently by students at home. The electronic module is the right solution that can be taken, especially for the Revolutionary Era 4.0 which encourages the learning process to integrate technology to improve the quality and efficiency of education.